MiR‐152/LIN28B axis modulates high‐glucose‐induced angiogenesis in human retinal endothelial cells via VEGF signaling. Issue 2 (14th October 2019) - Fu, Xiaolin; Ou, Bo
Abstract: Diabetic retinopathy (DR) is a serious complication of diabetes contributing to blindness in patients. Inhibiting retinal neovascularization is a potent strategy for diabetic retinopathy treatment. Reportedly, the stable expression of lin‐28 homolog B (LIN28B), a member of the highly conserved RNA‐binding protein LIN28 family, could promote vascular endothelial growth factor (VEGF) expression; herein, we investigated the role and mechanism of LIN28B in diabetic retinopathy progression from the perspective of microRNA (miRNA) regulation. We identified miR‐152 as a miRNA that may target the LIN28B 3′‐untranslated region and can be significantly downregulated under high‐glucose (HG) condition. The expression of miR‐152 was remarkably suppressed, whereas the expression of LIN28B was significantly increased under HG condition within both human retinal endothelial cells (hRECs) and retinal microvascular endothelial cell line (hRMECs). miR‐152 overexpression significantly suppressed, while LIN28B overexpression promoted the angiogenesis and the protein levels of proangiogenesis factors in both hRECs and hRMECs. More importantly, LIN28B overexpression could remarkably attenuate the effect of miR‐152 overexpression. In summary, miR‐152 overexpression could inhibit HG‐induced angiogenesis in both hRECs and hRMECs via targeting LIN28B and suppressing VEGF signaling. Further, in vivo experiments are needed for the application of miR‐152/LIN28B axis in the treatment for diabetic retinopathy. Abstract : miR‐152 overexpression could inhibit HG‐induced angiogenesis in both human retinal endothelial cells and retinal microvascular endothelial cell line via targeting LIN28B and suppressing vascular endothelial growth factor signaling. Further, in vivo experiments are needed for the application of miR‐152/LIN28B axis in the treatment for DR.